Low carbohydrate high fat diet: history and its impact on health - Lakshmi Deepika Patchva; Sankar Kurli (International Journal of Basic & Clinical Pharmacology, 2026)
The low carbohydrate high fat (LCHF) diet is a way of eating that restricts the amount of carbohydrates and increases the amount of healthy fats that you eat to optimize your health and nutrition. Consuming fats has very little direct effect on blood glucose levels and, as a result, does not lead to an increase in insulin levels. The principle of the LCHF diet is to replace carbohydrate intake with fat, thus reducing insulin levels and increase the body’s ability to utilize its own fat stores for energy.